Hydroxychloroquine and maintenance immunosuppression use in kidney transplant recipients: Analysis of linked US registry and claims data. Issue 12 (22nd November 2020) - Lentine, Krista L.; Lam, Ngan N.; Caliskan, Yasar; Alhamad, Tarek; Xiao, Huiling; Schnitzler, Mark A.; Chang, Su‐Hsin; Axelrod, David; Segev, Dorry L.; McAdams‐DeMarco, Mara; Kasiske, Bertram L.; Hess, Gregory P.; et al.
Abstract: Hydroxychloroquine (HCQ) is an antimalarial drug with immunomodulatory effects used to treat systemic lupus erythematosus (SLE) and scleroderma. The antiviral effects of HCQ have raised attention in the context of the COVID‐19 pandemic, although safety is controversial. We examined linkages of national transplant registry data with pharmaceutical claims and Medicare billing claims to study HCQ use among Medicare‐insured kidney transplant recipients with SLE or scleroderma (2008–2017; N = 1820). We compared three groups based on immunosuppression regimen 7 months‐to‐1 year post transplant: (a) tacrolimus (Tac) + mycophenolic acid (MPA) + prednisone (Pred) (referent group, 77.7%); (b) Tac + MPA + Pred + HCQ (16.5%); or (c) other immunosuppression + HCQ (5.7%). Compared to the referent group, recipients treated with other immunosuppression + HCQ had a 2‐fold increased risk of abnormal ECG or QT prolongation (18.9% vs. 10.7%; aHR, 1.12 1.963.42, p = .02) and ventricular arrhythmias (15.2% vs. 11.4%; aHR, 1.00 1.813.29, p = .05) in the >1‐to‐3 years post‐transplant. Tac + MPA + Pred + HCQ was associated with increased risk of ventricular arrhythmias (13.5% vs. 11.4%; aHR, 1.02 1.542.31, p = .04) and pancytopenia (35.9% vs. 31.4%; aHR, 1.03 1.311.68, p = .03) compared to triple immunosuppression without HCQ. However, HCQ‐containing regimens were not associated with an increased risk of death or graft failure. HCQ may be used safely in selected kidney transplant recipients in addition to their maintenance immunosuppression, although attention to arrhythmias is warranted.